Self-Care Amongst First-Year Teachers - Leia Baker (Networks: An Online Journal for Teacher Research, 2020)
This paper explores a study completed with two first-year teachers over a three-month period while self-care strategies were suggested and practiced. The paper discusses the impact that practicing and not practicing self-care has on first-year teachers’ attitudes and attendance. It also includes firsthand accounts from journal entries completed by both first-year teachers.
Keywords: Teacher self-care; first-year teachers; wellness; well-being